Single-subject analyses of magnetoencephalographic evoked responses to the acoustic properties of affective non-verbal vocalizations - Salvia, Emilie; Bestelmeyer, Patricia E. G.; Kotz, Sonja A.; Rousselet, Guillaume A.; Pernet, Cyril R.; Gross, Joachim; Belin, Pascal (Frontiers in Neuroscience, 2014)
Magneto-encephalography (MEG) was used to examine the cerebral response to affective non-verbal vocalizations (ANVs) at the single-subject level. Stimuli consisted of nonverbal affect bursts from the Montreal Affective Voices morphed to parametrically vary acoustical structure and perceived emotional properties. Scalp magnetic fields were recorded in three participants while they performed a 3-alternative forced choice emotion categorization task (Anger, Fear, Pleasure). Each participant performed more than 6000 trials to allow single-subject level statistical analyses using a new toolbox which implements the general linear model (GLM) on stimulus-specific responses (LIMO-EEG). For each participant we estimated ‘simple’ models (including just one affective regressor (Arousal or Valence)) as well as ‘combined’ models (including acoustical regressors). Results from the ‘simple’ models revealed in every participant the significant early effects (as early as ~100 ms after onset) of Valence and Arousal already reported at the group-level in previous work. However, the ‘combined’ models showed that few effects of Arousal remained after removing the acoustically-explained variance, whereas significant effects of Valence remained especially at late stages. This study demonstrates (i) that single-subject analyses replicate the results observed at early stages by group-level studies and (ii) the feasibility of GLM-based analysis of MEG data. It also suggests that early modulation of MEG amplitude by affective stimuli partly reflects their acoustical properties.